Effectiveness and Acceptability of Telerehabilitation in Physical Therapy during COVID-19 in Children: Findings of a Systematic Review - Asma Alonazi (MDPI AG, 2021)
The goal of this systematic review was to determine the efficacy and acceptability of telerehabilitation in physical therapy (PT) and parental acceptance during the COVID-19 pandemic in children. In 2021, an electronic search of academic articles was performed using databases such as Embase, PubMed and Scopus. One-hundred and one articles did not satisfy the eligibility criteria after deleting duplicates and reviewing abstracts, while 16 papers did not meet eligibility after reviewing complete texts. Hence, full texts for 13 articles were retrieved, which were incorporated in the review. All these studies were observational studies assessing the effectiveness and acceptability of telerehabilitation in PT required for diverse conditions in children during the COVID-19 pandemic. All included studies revealed a positive effect of telerehabilitation in PT during the COVID-19 pandemic in children with different conditions. Moreover, the included studies revealed that both rehabilitation professionals and parents or caregivers of children were satisfied with the telerehabilitation services provided remotely. Thus, telerehabilitation appears to be a suitable and convenient strategy to offer remote services to children in need but cannot visit in person due to COVID-19. The existing evidence shows that telerehabilitation can be considered effective for children who need PT for any health condition mainly during the pandemic. However, due to the dearth of studies in this area, exploring this topic is recommended mostly in low-middle-income countries with poor access to health care services and limited resources.